U.S Policy & Geopolitical Dynamics in the Middle East: Shifting Decision from Barrack Obama (2012-2016) to Donald Trump (2017) - Hendra Manurung; Albert Barita Sihombing (President University, 2017)
Afghanistan, a catastrophe in Iraq that helped destabilize vast swaths of the Middle East, an unconstitutional war in Libya that created a power vacuum exploited by ISIS, and a drone war that has killed hundreds of innocents in a half-dozen countries. The last two presidents campaigned against wars and won. The more interventionist candidate had lost every election since 2008. On 20 January 2017 Donald J. Trump is inaugurated as nation‟s 45th U.S President, and currently he is desperate. He is flailing from failure to failure in domestic policy, with dismal approval ratings and no clear way to increase them, except by trying to exploit the American public‟s historic tendency to rally around a president at war in implementing the U.S foreign policy. There has never been a stronger case for preemptively reining in a president‟s ability to unilaterally launch military strikes on foreign countries that are not attacking the U.S. To allow a man of Trump‟s character to retain that power, after its expansion by decades of presidents who pushed it beyond the bounds of the Constitution, would be folly.